Kalimat Tanya dalam Bahasa Sasak: Interrogative Sentence in Sasak - Lalu Erwan Husnan (Balai Bahasa Provinsi Papua, 2021)
This writing is aimed at giving more detil descriptiom on interrogative sentence in standard dialectal of Sasak. Descriptive-qualitative method is used. This method uses natural-empirical data. The data is standard dialectal a-e (Pujut) of Sasak. Data is collected in two main regencies which occupied by Sasak speakers. They are Central Lombok and West Lombok which focused in Batukliang Utara, East Praya, Pujut, and Kuripan Utara. Data collected through direct interview with native speakers of Sasak. The data is analized by agih method using six techniques. The analysis of interrogative sentences is done into eight kinds of question words. It is shown that there is another structure of interrogative sentence other than common structure of question words which always exist at the beginning of sentences. This structure allows questions words to be at the middle. The sentence constructed is grammatically dan semantically accepted in Sasak.